Pengudusan Gereja: Melihat Kembali Atribut Gereja yang Kudus - Waskito, Pranazabdian (STT Reformed Injili Internasional, 2024)
This article presents ideas on how to view the attributes of a holy church. The purpose is motivated by the misunderstanding of the church's holiness with the church's existence in the world. This existence gives rise to the notion that the church has sinfulness and weakness. This view can make the church's holiness attribute vague. To answer the background of the problem, this paper uses the content analysis method of literature review. The author finds that the attributes of a holy church cannot be clashed with the reality of the pilgrim's church in the world with the weaknesses and sins committed by its people. Ecclesiological dimensions can help reveal how to view the church's holiness. The attributes of a holy church remain holy because they are related to God's act of sanctifying His church.